Pengaruh Model Pembelajaran STAD berbantuan Media Jam Putar ASEAN terhadap Motivasi Belajar Siswa pada Materi ASEAN di Kelas 6 - Anggraeni, Yulia; Attalina, Syailin Nichla Choirin; Muhaimin, Muh (Jurnal Simki Pedagogia, 2025)
Low student learning motivation, especially at the elementary school level, can be caused by inaccuracy in the use of learning models and media. This study aims to determine the effect of the STAD learning model assisted by the ASEAN Rotating Clock media on the learning motivation of grade VI students of SDN 1 Guyangan. The study used a quantitative method with a one group pretest-posttest experimental design. Data were collected through questionnaires and analyzed using normality tests, homogeneity, and hypothesis tests (t-test and regression/F test) through SPSS 25. The results showed an increase in the average score from the pretest (52.90%) to the posttest (77.25%). The t-test produced a sig value of 0.00 <0.05 and tcount> ttable (21.506> 2.7961), while the F test showed sig 0.00 <0.05 and fcount> ftable (26.612> 4.325). Thus, there is a significant effect of the use of the STAD model with the ASEAN Rotating Clock media on student learning motivation.